NATIONAL VALUES IN JARAN PEGON KEDIRI CULTURE - Ameilia, Neti; Sukmawan, Sony (JURNAL KONFIKS, 2025)
Along with the development of the times, national values are increasingly eroded by foreign cultures that easily enter Indonesia. An example of the influence of foreign culture is the Korean Wave, which Indonesian teenagers widely love. This is caused by the weakness of national values possessed by the young generation in Indonesia. National values themselves need to be instilled from an early age until adolescence to avoid various problems that often occur in the teenage environment, such as the decline in politeness and the forgetting of Pancasila values among teenagers. National values need to be instilled by utilizing various available media. One of the media that can be used is the Jaran Pegon art, which still has many fans to this day. Therefore, this study aims to explain the national valuescontained in the Jaran Pegon culture, which is typical of Kediri. This study is classified as qualitative research, utilizing interview techniques with relevant parties to gather the necessary information. The results obtained from this study reveal the presence of strong national values, such as divinity, unity, and patriotism, in the art of Jaran Pegon and Javanese songs used within this art form. With many enthusiasts spread across Kediri and its surroundings, Jaran Pegon has the opportunity to instill national values in the general public through its performing arts.